Relationship between the clinical course of chronic osteomyelitis of the lower jaw and the expression of receptor molecules of cellular activation (LLC "Endo Press", 2020)
Osteomyelitis of the jaw bones is an infectious inflammatory process of odontogenic or post-traumatic nature, which in recent years has significantly changed its clinical picture. The purpose of the study was to study the relationship between the parameters of the immune status in patients with chronic osteomyelitis of the lower jaw and the clinical course to elucidate the prospects for the use of immunotropic drugs. Results. It is concluded that the study of the parameters of systemic immunity in patients with chronic osteomyelitis followed by appointment of immunotrophic polyoxidonium preparation, increases the effectiveness of complex treatment of patients.